Water Pollution of Jembatan II River as an Impact of Degradation in the Upperwater of the River Basin - Auldry F. Walukow; I Nyoman Sukarta; Janviter Manalu; Johnson Siallagan; Albert Lumbu; Triwiyono; Wilda Wijayani Pamangin; Markus Budi; Ersan Awidya Pratama; Sonny Kristian Tabuni (Universitas Pendidikan Ganesha, 2026)
The problem that occurs in the Jembatan 2 River is that the river is cloudy every day. The problem around the Jembatan II River is the high rate of erosion and sedimentation rate due to forest degradation in the upstream of the Sentani Watershed. This research was conducted in the Jembatan 2 River, Jayapura Regency. This research aims to analyze the water quality status of Lake Sentani, (2) Analyze the water quality status of the Jembatan II River. The data collection method is measuring river water samples and the strategy analysis method uses a SWOT questionnaire. The data analysis technique is the Pollution Index (IP) method and the SWOT method. The results of the study show that the water quality status of Lake Sentani has been lightly polluted with a Pollution Index value of 3.1. The Jembatan 2 River has been lightly polluted with a Pollution Index of 3.12. The parameters that have exceeded the quality standards in the Jembatan 2 River are the TSS, BOD, COD, and PO4-P parameters. The recommended policy model is the WT (Weaknesses-Threats) strategy with coordinates (-0.72; -0.80), the policy recommendations are to maximize the natural potential of the lake so that the community around the lake does not encroach on the forest, the need for effective reforestation in the Cycloop CA buffer zone, the implementation of building regulations on the right and left of the river, river revitalization at the inlet of Lake Sentani, regular socialization of regulations to the community around the area, and rehabilitation of critical lands in the buffer zone.